Implementasi Teknologi Digital Untuk Mengembangkan Income Generating Desa Wisata Keling Kabupaten Kediri Jawa Timur - Khoirur Rozaq (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
Tourism villages have recently become a list of destinations for domestic tourists. One of the tourist villages in East Java is the Keling Tourism Village in Kediri Regency. This research focuses on the application of digital media to Keling tourism village products as an effort to grow income generation. The aim is to find out how people use digital media to market Keling tourism village products. The research was carried out using primary data taken from direct observation as well as interviews with full parties. For supporting data using a systematic literature review. The approach to this research is qualitative-descriptive. The first research finding is that there are quite a lot of tourism potentials in the Keling tourist village. Second, the use of digital media empirically increases income which is quite satisfactory. Third, digital media really helps managers and tourists to get to know more about and improve the quality and quantity of Keling tourism village products.